Advanced tissue engineering scaffold design for regeneration of the complex hierarchical periodontal structure - Costa, P. F. (2014)
Aim: This study investigated the competence of an osteoinductive biphasic scaffold to simultaneously regenerate alveolar bone, periodontal ligament and cementum. Materials and Methods: A biphasic scaffold was built by attaching a fused deposition modeled bone compartment to a melt electrospun periodontal compartment. The bone compartment was coated with a calcium phosphate layer for increasing osteoinductivity, seeded with osteoblasts and cultured in vitro for 6 weeks. The resulting constructs were then complemented with the placement of PDL cell sheets on the periodontal compartment, attached to a dentin block and subcutaneously implanted into rats for 8 weeks. Scanning electron microscopy, x-ray diffraction, alkaline phosphatase and DNA content quantification, confocal laser microscopy, micro computerized tomography and histological analysis were employed to evaluate the scaffold’s performance. Results: The in vitro study showed that alkaline phosphatase activity was significantly increased in the CaP coated samples and they also displayed enhanced mineralization. In the in vivo study, significantly more bone formation was observed in the coated scaffolds. Histological analysis revealed that the large pore size of the periodontal compartment permitted vascularization of the cell sheets, and periodontal attachment was achieved at the dentin interface. Conclusions: This work demonstrates that the combination of cell sheet technology together with an osteoinductive biphasic scaffold could be utilized to address the limitations of current periodontal regeneration techniques.